Za boga, narod in domovino! Katero? - Klabjan, Borut (Acta Histriae, 2022)
The article examines the role of the Bohemian and Moravian Clergy in Istria in the first decades of the Twentieth Century. It analyses the reasons of their presence in the area starting from the mid-Nineteenth Century, when the bishop of Trieste/Trst and Koper/Capodistria Legat initiated fulfilling vacant positions with priests from other parts of the Habsburg monarchy, a practice developed by his successor Glavina. In the last decades of the Nineteenth Century several dozens of students from Bohemia and Moravia attended the seminary in Gorizia/Gorica. Most of them left for Istria after schooling and Fran Novljan, a local intellectual and politician noted that “there were little parishes in the internal parts of Istria where a bohemian priest was not operating”. Many of them integrated fully in the new communities and became fundamental reference points for local societies, in religious, but also in social, economic and cultural terms. This article uses their case to address the question of multiple options of citizenship and State affiliation in the changed context of post-World War I Istria, which was occupied by Italian forces in November 1918 and later annexed to the Kingdom of Italy. Following the attitude of Italian authorities and the repressive measures towards unwanted individuals, it opens a wide range of questions related to inclusion and exclusion in European post-imperial borderlands.
Keywords: Austria-Ungheria; Austro-Hungary; Avstro-Ogrska; Cecoslovacchia; Czech priests; Czechoslovakia; češki duhovniki; češkoslovaška; fascism; fascismo; fašizem; Istra; Istria; Italia; Italija; Italy; Moravian priests; moravski duhovniki; preti boemi; preti moravi